Impact of the Pd2Spermine Chelate on Osteosarcoma Metabolism: An NMR Metabolomics Study - Lamego, Inês (2017)
A metabolomics study of Pd2Spermine(Spm) on osteosarcoma MG-63 and osteoblastic HOb cells is presented to assess the impact of the potential palladium drug on cell metabolism compared with cisplatin (cDDP). Despite its higher cytotoxicity, Pd2Spm induced lower (and reversible) metabolic impact on MG-63 cells and the absence of apoptosis; conversely, it induced significant deviations in osteoblastic amino acid metabolism. However, when in combination with doxorubicin and methotrexate, Pd2Spm induced strong metabolic deviations on lipids, choline compounds, amino acids, nucleotides, and compounds related to antioxidative mechanisms (e.g., glutathione, inositol, hypoxanthine), similarly to the cDDP cocktail. Synergetic effects included triggering of lipid biosynthesis by Pd2Spm in the presence of doxorubicin (and reinforced by methotrexate) and changes in the glycosylation substrate uridine diphosphate acetylgalactosamine and methionine and serine metabolisms. This work provides promising results related to the impact of Pd2Spm on osteosarcoma cellular metabolism, particularly in drug combination protocols. Lipid metabolism, glycosylation, and amino acid metabolisms emerge as relevant features for targeted studies to further understand a potential anticancer mechanism of combined Pd2Spm.